BDI, Gold Price and Economic Growth - Bildirici, Melike; Kayikci, Fazil; Onat, Isil Sahin (ELSEVIER SCIENCE BV, 2016)
Since its establishment, the Baltic Dry Index has become one of the foremost indicators on the cost of shipping as well as an important barometer on the volume of worldwide trade and manufacturing activity. In this paper, the MSIH(3)-VAR(3) model is selected to analyse the relationship between BDI, Gold prices and economic growth for the United States. The BDI, gold prices and GDP are cointegrated for the United States. The crisis regime tends to last 1 years on average, while Regime 2 is comparatively more persistent with 6.46 years. Finally, Regime 3 which corresponds to high growth tends to last 1.16 years, on average. The crisis regime of the economy is the most persistent regime in the US. Thus, the BDI and gold prices can be used as an indicator of crisis in GDP growth for the United States. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: BDI; Gold prices; Economic Growth; MS-VAR; TIME-SERIES; MODEL; Business & Economics